2015
DOI: 10.1590/1413-81232015209.00442015
|View full text |Cite|
|
Sign up to set email alerts
|

Distribuição espacial da obesidade em área urbana no Brasil

Abstract: )* Mediana e Intervalo Interquartílico. Na análise comparativa das características dos indivíduos nos conglomerados de obesos e não obesos não foram verificadas diferenças significativas entre as variáveis analisadas (p > 0,05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Previous studies have shown that less economically privileged areas have worse health conditions when compared to more privileged areas both between countries 5 and within the same country, revealing the unequal geographical distribution of diseases [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that less economically privileged areas have worse health conditions when compared to more privileged areas both between countries 5 and within the same country, revealing the unequal geographical distribution of diseases [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Además, existe el hecho de que, en promedio, sobreviven con un ingreso familiar de 2.36 salarios mínimos, lo que justifica su insatisfacción. La obesidad es inversamente proporcional a la clase social y la población más pobre es la que más sufre debido a la obesidad y sus enfermedades (28) .…”
Section: Discussionunclassified
“…Geographical distribution has been used to study diseases in epidemiological analyses. [24][25][26][27] This tool becomes important in the study of genetic diseases when there is a possibility of intervention with genetic guidance, as in the case of increased incidence of healthy carriers of the gene that causes the condition. Therefore, knowing the regions of Sergipe with higher incidence of heterozygous individuals is useful to guide the planning of health care actions for patients with SCA, as well as informing the situation to asymptomatic carriers and counseling the families, which may change the incidence profile of SCD in this population.…”
Section: Discussionmentioning
confidence: 99%